2021
DOI: 10.1002/adfm.202100178
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Superparamagnetic Ring (tSPRing) for Droplet Manipulation

Abstract: The manipulation of droplets via a magnetic field forms the basis of a fascinating technology that is currently in development. Often, the movement of droplets with magnets involves adding magnetic particles in or around the droplet; alternatively, magneto responsive surfaces may also be used. This work, presents and characterizes experimentally the formation and properties of a tunable superparamagnetic ring (tSPRing), which precisely adjusts itself around a water droplet, due to liquid–liquid interaction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…[33][34][35][36] Nevertheless, previous research has mainly focused on the simple splitting and horizontal self-assembled structures of the ferrofluid droplets induced by magnetic-field-gradient forces, which typically exhibit a single spike-array mode. [37,38,41,45] The controlled splitting behavior of ferrofluid droplets under magnetic torque is also overlooked. Moreover, the horizontal and vertical dynamic self-assembly behavior of ferrofluid droplets still needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Nevertheless, previous research has mainly focused on the simple splitting and horizontal self-assembled structures of the ferrofluid droplets induced by magnetic-field-gradient forces, which typically exhibit a single spike-array mode. [37,38,41,45] The controlled splitting behavior of ferrofluid droplets under magnetic torque is also overlooked. Moreover, the horizontal and vertical dynamic self-assembly behavior of ferrofluid droplets still needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 10b, various types of droplet manipulation techniques have been realized on surfaces. Nasirimarekani et al 119 presented a tunable superparamagnetic ring (tSPRing), which was composed of an oil‐based ferrofluid. Under the action of a magnetic field, the tSPRing could manipulate the droplets in a powerful, controllable and programmable way (Figure 10c).…”
Section: Droplet Manipulation Based On Active Strategiesmentioning
confidence: 99%
“…(c) Ferrofluid spikes deposited on the surface, holding the water droplets in place, when a magnetic field over the saturation magnetization of the ferrofluid was applied to the tSPRing. Reproduced with permission 119 . Copyright 2021, Wiley‐VCH.…”
Section: Droplet Manipulation Based On Active Strategiesmentioning
confidence: 99%
“…Because of so many superiorities such as remote operability, and rapid response, dynamic control of magnetic droplets under a magnetic field has attracted more and more attention. [41][42][43][44] Applying superhydrophobic surfaces with high water-repellent ability and slippery surfaces with low friction can avoid lots of challenges during the traditional manipulation process such as mass loss and cross contamination. [45][46][47][48] For example, Jiang et al reported no-loss transportation of a magnetic droplet by a high adhesive superhydrophobic polystyrene film; [49] Guo et al demonstrated regulation of the sliding state of a magnetic droplet on a superhydrophobic surface by adjusting the intensity of the magnetic field; [50] Rigoni et al demonstrated an unique stick-slip motion of a magnetic droplet on a slippery surfaces under the action of the patterned magnetic field; [51] we recently also reported the in-situ on/off sliding control of a superparamagnetic microdroplet on a superhydrophobic surface.…”
Section: Introductionmentioning
confidence: 99%